Interaksi Sosial Masyarakat Multikultural Madinah Perspektif Kajian Hadis: Interaksi Sosial Masyarakat Multikultural Madinah Perspektif Kajian Hadis - Ali Mohtarom; Syaifullah (Mu'allim, 2025)
This qualitative research analyzes the social conditions of the Madinah community during Prophet Muhammad's era and the hadiths governing their social interactions. It highlights Madinah's socio-political environment marked by conflict, mainly between the Aus and Khazraj tribes. Prophet Muhammad addressed this by drafting the Constitution of Madinah, a foundation of multiculturalism. His role as head of state laid the groundwork for multicultural education, emphasizing Islamic values like justice, egalitarianism, and peace through rahmatan lil alamin theology. His exemplary conduct promoted tolerance. Additionally, his hadiths regulated social conduct, promoting inclusivity in multicultural society through greetings, handling the deceased, family ties, prayers, and converting Jews to Islam. They also prohibited killing women, children, laborers, and harming non-Muslims, further fostering a harmonious multicultural environment.